2017
DOI: 10.1007/s00520-017-3816-3
|View full text |Cite
|
Sign up to set email alerts
|

Totally implantable venous access ports: a prospective long-term study of early and late complications in adult patients with cancer

Abstract: This study demonstrates excellent tolerability, with only occasional complications. Most of these occurred during the year following implantation. A TIVAP may also be left in place for an extremely long time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 24 publications
3
51
2
2
Order By: Relevance
“…24 The late complications rate from long-term use was 5.45% (3/55), which was consistent with the reported literature. 12,25 Two patients had catheter-related infections on the 127th and 369th days after operation. The blood culture showed Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 The late complications rate from long-term use was 5.45% (3/55), which was consistent with the reported literature. 12,25 Two patients had catheter-related infections on the 127th and 369th days after operation. The blood culture showed Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 99%
“…At present, ultrasound (US)‐guided percutaneous puncture of the internal jugular vein (IJV) and subclavian vein (SCV) are the two main approaches for TIVAD . Complications include hemothorax, pneumothorax, catheter displacement and catheter rupture, which delay the treatment of the disease and reduce the effective utilization rate of the transfusion port …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some drugs are toxic to the veins particularly peripheral veins . So the implantation of a TIVAP is required as its advantage of easy access of central veins . It was reported that there were significant less complications in TIVAPs than what in other accesses for chemotherapy and it could be used in entire treatment cycle safely .…”
Section: Comparison Of Achievement Ratio and Operation Duration By DImentioning
confidence: 99%
“…2 So the implantation of a TIVAP is required as its advantage of easy access of central veins. 3 It was reported that there were significant less complications in TIVAPs than what in other accesses for chemotherapy and it could be used in entire treatment cycle safely. 4 Generally, in TIVAPs implantation, we use the basilic vein, subclavian vein, external jugular vein, or the internal jugular vein (IJV) as puncture sites.…”
mentioning
confidence: 99%